Using Behavioural Reasoning Theory to Explore Reasons for Dietary Restriction: A Qualitative Study of Orthorexic Behavioural Tendencies in the UK - Mitrofanova, Elina; Pummell, Elizabeth K. L.; Mulrooney, Hilda M.; Petróczi, Andrea (Frontiers in Psychology, 2021)
Orthorexia Nervosa (ON) has gained increased attention in academia since 1997. However, like other ‘Exia’ conditions, there is debate around its inclusion in the Diagnostic and Statistical Manual of Mental Disorders. This study aimed to examine the experiences of those following a diet indicative of ON in the United Kingdom. This information is essential to the development of diagnostic criteria and classification of ON. Behavioural Reasoning Theory was used to explore reasons contributing to the development of ON. Ten individuals (two males and eight females), aged 23 to 35 years, took part in semi-structured interviews. Inductive thematic analysis was used to analyse the results. Four themes emerged from the data - journey, social, rules/control, and ethical considerations which highlighted contributing factors to the development of ON behaviours, the impact of these behaviours on individuals’ social lives, and a strive for control. These findings are the first to suggest that ON involves a more complex set of behaviours than current definitions and proposed diagnostic criteria suggest and highlight the need to consider a variety of reasons for restricted diet when developing diagnostic criteria, screening tools, and classification in the DSM.